COMPANY DESIGN FLASH -BASED PROFILES AS A MEANS OF SUPPORTING PROMOTIONAL MEDIA: Studies case: CV. Indoprinting Tembalang - Ireng Ario Seto; Setiyo Prihatmoko (University of Science and Computer Technology, 2024)
The development of information media is increasing rapidly. The need for information media, both print and electronic media, is a top priority for society in the current era. Of course, this development also influences how it is applied to various media so that people can easily obtain this information. As more and more people need information, many business people are competing to take the opportunity to set up a printing press. Digital printing is a method of printing digital-based images, which are usually in the form of files , which can then be printed directly on various media in an instant and fast way . With digital printing, people can easily apply information media quickly. Digital printing is the right solution for people who want to advertise their products/merchandise so they sell quickly. Indoprinting is here to meet the needs of people in the Semarang area and surrounding areas to fulfill their printing needs. There are obstacles faced by Indoprinting, one of which is that there are still many who don't know what prints can be processed at Indoprinting. The way to overcome this, Indoprinting will develop an electronic company profile which is useful for introducing what products and services are available at Indoprinting. The company profile can be placed in the waiting room so that customers can access it easily, and it can also be used by the team marketing in presenting the big picture of the company to clients. Having this company profile can help customers who don't know more about the services and products available at Indoprinting.